Intellectual Property Rights in Malaysia - S. Rajendran (1997)
In the light of Malaysia's determination to move into the Information Age by the turn of the century, mainly through the development of the Multimedia Super Corridor, it is important to evaluate the role of the Intellectual Property Rights in Malaysia. This paper, therefore,traces the development of laws in respect of Intellectual Property Rights in Malaysia and the problem faced in ensuring that the conflicting interests in the free flow of information and the need for protection of individual proprietary rights are balanced. The objective of the study is to examine the ways and means used for striking a balance between free flow of information and the protection of individual rights. The methodology adopted is exploratory and comparative. It is exploratory owing to the novelty of the subject matter and comparative as the experiences of advanced nations in this field are drawn upon to enable an appropriate model to be developed for Malaysia. As Intellectual Property Rights are related to information technology, which is charactarised by change and challenge, the issues involved, like those inherent in the Internet and the place of the consumer in these Rights, are noted. Overall, the observance of Intellectual Property Rights is expected to provide Malaysia with an edge in the competitive world of international trade and move Malaysian economy to a service orientated one through the Multimedia Super Corridor. In addition, the promotion of Intellectual Property Rights and the development of the Multimedia Super Corridor signals the move towards an immersion into information technology to stay abrest/ahead of developments in the fast approaching process of globalisation.